Overcoming Language Barriers in Contracts – A South African Perspective - M. van Eck (BRICS Law Journal, 2024)
Language forms the basis of written contracts, but the use of language may also function as a barrier to contracting parties, particularly when the parties are not proficient in the commercial language of choice, such as English in the case of South Africa. The plain language movement and specifically legislative interventions have placed significant pressure on lawmakers to reform the use of traditional legal English, and consequently, traditional drafting styles. However, many contracts continue to exhibit convoluted language, legalese and poor visual appeal, which ultimately functions as a language barrier for many people. This article examines the various language barriers that exist in contracts from a South African perspective. It does so by assessing the barriers that exist under first, the common law (or the so-called default rules), second, the use of standard contracts, and third, the resistance to the use of plain language as well as the limited application of existing plain language legislation in certain types of contractual engagements. The author proposes dismantling the language barriers by adopting both textual and visual communication devices in order to achieve clear and comprehensible language in all types of contracts. Furthermore, it is suggested that such communication devices should not necessarily be limited to consumer contracts that are legislatively required to comply with plain language requirements. It is only by dismantling existing language barriers that social justice within contracts can be achieved in a society with diverse language proficiencies, such as South Africa. Therein, this article offers insights that are relevant not only within the South African context but also for countries that may face similar language barriers characterised by multiple languages and varying language proficiencies within their populations.